Amelia's guide to gossip : the good, the bad, and the ugly - Moss, Marissa (Simon & Schuster Books for Young Readers, 2006)
To spread gossip, you need to know stuff and, you need to know how to tell it in an exciting way--but you have to be careful, since gossip is never nice, is the summary of the story.